Operasional Bank Sampah Dalam Meningkatkan Pengurangan Sampah di Kecamatan Duren Sawit - Viery Ardiansyah; Pramiati Purwaningrum; Ratnaningsih Ruhiyat (Jurnal Serambi Engineering, 2023)
Waste Bank is one of the options to reduce solid waste in solid waste management. The planning purposes is to plan waste reduction through the Waste Bank with the 3R concept to support solid waste management in Duren Sawit District. The method used for sampling the generation rate and composition of waste in Duren Sawit Subdistrict is in accordance with SNI 19-3964-1994; making observations to obtain data on waste management at the Waste Bank; and conducting interviews both verbally and with questionnaires regarding community participation. Based on the results of the study, the waste generation rate in Duren Sawit District is 0.6 kg/person/day with a composition of 70% organic waste and 30% inorganic waste. The potential for waste recycling that can be done in Duren Sawit District is 27%. By the end of the planning year, the Waste Bank has the potential to reduce waste by 37% of waste generation. To achieve this reduction, the Waste Bank needs to improve services and community participation as customers and noncustomers. The Waste Bank will be optimized in stages according to the percentage growth of Waste Bank customers in each kelurahan. In the first stage, the optimization of the Waste Bank is targeted to reach 50% of the total households in the Duren Sawit Sub-district. In long-term planning, the Waste Bank plays an important role in the aspect of waste management.